2000
DOI: 10.1016/s0735-1097(99)00590-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of T-wave alternans and late potentials used to predict arrhythmic events after myocardial infarction

Abstract: The combined assessment of TWA and LP was associated with a high positive predictive value for an arrhythmic event after acute MI. Therefore, it could be a useful index to identify patients at high risk of arrhythmic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(132 citation statements)
references
References 28 publications
4
125
0
3
Order By: Relevance
“…[18][19][20][21] DAD is known to be augmented if intracellular calcium overload occurs in the presence of an abnormal ryanodine receptor. 14,[19][20][21] Altered calcium cycling is now believed to result in alteration of repolarization and T-wave alternans and T-wave alternans is established as a strong predictor of arrhythmogenic risk, [22][23][24] but such an ECG marker of repolarization has not yet been evaluated in CPVT in which abnormal calcium cycling is highly possible. [17][18][19][20][21]25) We observed macroscopic alteration in the U-wave: alternans in 2 patients and a change in the polarity after a pause among 7 patients with CPVT.…”
mentioning
confidence: 99%
“…[18][19][20][21] DAD is known to be augmented if intracellular calcium overload occurs in the presence of an abnormal ryanodine receptor. 14,[19][20][21] Altered calcium cycling is now believed to result in alteration of repolarization and T-wave alternans and T-wave alternans is established as a strong predictor of arrhythmogenic risk, [22][23][24] but such an ECG marker of repolarization has not yet been evaluated in CPVT in which abnormal calcium cycling is highly possible. [17][18][19][20][21]25) We observed macroscopic alteration in the U-wave: alternans in 2 patients and a change in the polarity after a pause among 7 patients with CPVT.…”
mentioning
confidence: 99%
“…Since late potentials detected by SA-ECG reflect conduction abnormalities, they are considered to be a predictive marker of arrhythmic events in organic heart disease (Kuchar et al 1987;Ikeda et al 2000). On the other hand, the mechanisms of developing late potentials in Brugada syndrome are considered as being based on both repolarization and depolarization abnormality theory (Antzelevitch 2002;Huang et al 2009).…”
Section: Late Potentials By Sa-ecgmentioning
confidence: 99%
“…Depolarization abnormalities noted in these studies may contribute to the development of late potentials in patients with Brugada syndrome. It was previously reported that late potentials detected by SA-ECG play some roles in risk stratification for patients with type 1 ECG, in whom especially measurement of RMS40 in late potentials is useful to predict their arrhythmic events (Kuchar et al 1987;Ikeda et al 2000;Ajiro et al 2005;Huang et al 2009). However, the risk stratification strategy for patients with type 2 ECG remains to be established (Ikeda et al 2001;Ajiro et al 2005;Huang et al 2009).…”
Section: Late Potentials By Sa-ecgmentioning
confidence: 99%
See 1 more Smart Citation
“…T o assess the risk of Sudden Cardiac Death (SCD), several electrocardiograms (ECG)-based predictors have been proposed in [1]. Among these, T-wave alternans (TWA) is one of the most promising predictors of SCD [2,3], which is defined as a beat-to-beat change in the amplitude of the T-wave that repeats once every other beat.…”
Section: Introduction Microvolt T-wave Alternansmentioning
confidence: 99%